Knowledge Level, Motivational Factors, and Potential Barriers Toward Blood Donation Among MBBS Students - Ibrahim, Muhammad; Omarzai, Rahmat Gull; Bibi, Aqsa; Rehman, Mujeeb; Din, Gulab; Faisal Sultan, Muhammad Abdul Rab (Students' Supplement of Journal of Rawalpindi Medical College, 2024)
Background: Blood is almost needed in every hospital for surgeries, traumas, transplantations, pregnancy complications, and thalassemia patients. Objectives: The objectives of our studies were as follows: To assess the knowledge level of MBBS students about blood donation, to identify the obstacles and difficulties facing MBBS students towards blood donation, and to determine the factors that influence young people to donate blood. Methods: A cross-sectional descriptive study involving 300 participants was carried out at (study setting removed to maintain anonymity). A stratified sampling technique was used. A printed self-administered questionnaire was used. The responses were recorded on a 5-point Likert scale. Results: Only 76 out of 300 (25.3%) were blood donors. The chi-square test was used to find out the association of blood donation status with gender and knowledge level score. Men were more likely to donate blood than women. However, the blood donation status and knowledge level of participants were not related and scores of donors and non-donors were almost the same. Blood donors reported that the most common motivators for donating blood are to save other people's lives when someone they know is in need and feelings of self-satisfaction. Conclusion: More males donate blood than females, but knowledge level doesn’t affect blood donation, with donors motivated by saving lives and non-donors hindered by not being asked or not meeting criteria.